Gold nanobipyramid-embedded silver–platinum hollow nanostructures for monitoring stepwise reduction and oxidation reactions. Issue 46 (20th November 2020) - Xu, Juan; Yun, Qinru; Wang, Changshun; Li, Manman; Cheng, Si; Ruan, Qifeng; Zhu, Xingzhong; Kan, Caixia
Abstract : Gold nanobipyramid-embedded AgPt hollow nanostructures were synthesized under different conditions (temperature and surfactant) and are a promising surface-enhanced Raman scattering probe for monitoring stepwise reduction and oxidation reactions. Abstract : Metal hollow nanostructures based on gold nanobipyramids (Au NBPs) are of great interest for the combination of tunable plasmonic resonances and excellent physicochemical properties. Based on the core–shell Au NBP@Ag nanorods with desired sizes, herein we reported the synthesis and growth mechanism of Au NBP-embedded AgPt hollow nanostructures with tunable thickness and size. The Au NBP@AgPt nanoframes were obtained at lower temperature, in which cetyltrimethylammonium bromine (CTAB) was applied as a capping agent to guide the deposition of Pt atoms on the edges and corners of Au NBPs@Ag nanorods. With the increase of reaction temperature, the Au NBP@AgPt nanoframes convert into nanocages due to the atomic migration to the surfaces. The surface plasmon resonance of the Au NBP@AgPt hollow nanostructure shifts from red to blue, which is ascribed to the changes in coverage area and location site of the AgPt alloy. When CTAB was replaced by cetyltrimethylammonium chloride (CTAC), Au NBP@AgPt nanocages dominate the product. The surface roughness and thickness of the nanocages can be controlled by the temperature and the amount of Pt precursor. Moreover, Au NBP@AgPt hollow nanostructures show excellent surface-enhanced Raman scattering and exhibit remarkable stability in harsh environments. Taking into account the advantages of the plasmonic property (Au NBPs), catalytic activity (Pt) and plasmon-enhanced signal (Ag), the Au NBP@AgPt hollow nanostructures are a promising candidate for technological applications in catalytic reactions.